2019
DOI: 10.1103/physrevb.100.214312
|View full text |Cite
|
Sign up to set email alerts
|

Multielectron interference of intraband harmonics in solids

Abstract: High harmonic generation in solids provides us compact and coherent UV sources. Our simulations illustrate abnormal harmonic yield dependence on the intensity of driving or pre-excitation pulses. A multielectron interference model is proposed to reveal the mechanism of the extreme nonlinear optical phenomena. We find that the k-resolved intraband harmonic demonstrates different symmetry, phase, and amplitude, which can be observed by using a resonant pre-excitation pulse. The position of the interference minim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…5-7, a correct description of the intraband harmonics in the below-band-gap regime still requires the contributions from all the occupied orbitals to be coherently taken into account, as also found in Ref. [43].…”
Section: Fig 5 (A)mentioning
confidence: 84%
See 2 more Smart Citations
“…5-7, a correct description of the intraband harmonics in the below-band-gap regime still requires the contributions from all the occupied orbitals to be coherently taken into account, as also found in Ref. [43].…”
Section: Fig 5 (A)mentioning
confidence: 84%
“…Two main theoretical approaches to study HHG in solids include (i) the time-dependent Schrödinger equation (TDSE) for individual Bloch electrons with specific k values [25][26][27][28][29][30][31][32][33][34][35], and (ii) many-electron approaches such as the semiconductor Bloch equations (SBEs) [36][37][38][39][40][41][42][43][44][45][46] and the time-dependent density-functional theory (TDDFT) [23,[47][48][49][50][51][52][53][54][55][56]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here e is the elementary charge and a is the lattice constant. Similarly, expanding the fielddependent energy of a 1D single-band conductor in a power series of the crystal momentum k, it can be shown that the mth spectral component of the induced current has a leading term proportional to E m 0 , where E 0 is the laser electric field amplitude 25 . The intensity of the m-th harmonic would therefore scale as I m , where I is the driving laser intensity, for low enough I.…”
Section: Resultsmentioning
confidence: 99%
“…Here e is the elementary charge and a is the lattice constant. Similarly, expanding the field-dependent energy of a 1D single-band conductor in a power series of the crystal momentum k , it can be shown that the m th spectral component of the induced current has a leading term proportional to , where E 0 is the laser electric field amplitude 25 . The intensity of the m -th harmonic would therefore scale as I m , where I is the driving laser intensity, for low enough I .…”
Section: Resultsmentioning
confidence: 99%